2016
DOI: 10.1111/jdv.13649
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical cardiovascular disease and it's improvement after long‐term TNF‐α inhibitor therapy in severe psoriatic patients

Abstract: Patients with severe psoriasis exhibit signs of subclinical cardiovascular disease compared to control, and prolonged anti-TNF-α therapy has a potentially beneficial effect on these signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Treatment of psoriasis patients with TNF-α inhibitors may also have beneficial effects on the development of atherosclerosis and components of the metabolic syndrome. Anti-TNF-α therapy in patients with severe psoriasis has been shown to improve subclinical cardiovascular disease (abnormalities in echocardiogram) [ 13 ], improve coronary microvascular function (determined by transthoracic Doppler echocardiography) [ 274 ], and attenuate the progression in coronary artery disease (assessed by coronary computed tomography) [ 275 ]. Treatment of patients with moderate to severe psoriasis with adalimumab for 6 months led to improvement in endothelial function (brachial artery reactivity) and carotid arterial stiffness [ 276 ].…”
Section: Effects Of Anti-psoriasis Therapies On Cardiovascular Commentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment of psoriasis patients with TNF-α inhibitors may also have beneficial effects on the development of atherosclerosis and components of the metabolic syndrome. Anti-TNF-α therapy in patients with severe psoriasis has been shown to improve subclinical cardiovascular disease (abnormalities in echocardiogram) [ 13 ], improve coronary microvascular function (determined by transthoracic Doppler echocardiography) [ 274 ], and attenuate the progression in coronary artery disease (assessed by coronary computed tomography) [ 275 ]. Treatment of patients with moderate to severe psoriasis with adalimumab for 6 months led to improvement in endothelial function (brachial artery reactivity) and carotid arterial stiffness [ 276 ].…”
Section: Effects Of Anti-psoriasis Therapies On Cardiovascular Commentioning
confidence: 99%
“…In some studies (particularly large-scale epidemiological studies), patients were classified as severe psoriasis if they required systemic therapy (including methotrexate, retinoid, cyclosporine, biological agents, or phototherapy) [ 3 , 11 , 12 ]. In other studies, severe psoriasis was defined in terms of Psoriasis Area and Severity Index score (for example, PASI > 15) [ 13 ], or body surface area involvement (for example, BSA > 10%) [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In other studies evaluating subclinical myocardial dysfunction with STE imaging in patients with psoriasis or PsA, the mean age of the subjects was 46, 41.1, 51.8, 41, and 51.5 years. 7,11,21,22,31 In the present study, although the subjects had no risk factors for CVD and were relatively young, myocardial dysfunction was still assessed using STE.…”
Section: Discussionmentioning
confidence: 94%
“…Prolonged anti-TNF- α therapy has beneficial effects on the signs of subclinical cardiovascular disease in patients with severe psoriasis [ 27 ]. Studies have shown that, compared with nonbiologic disease-modifying antirheumatic drugs, TNF- α -blocking agents may contribute to the reduction of the risk of cardiovascular events in patients with rheumatoid arthritis [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%